Age, Gender, and Preoperative LVEF Influence on ICU Length of Stay After CABG - Rara Amourra Arviolla; Budiana Rismawan; Muchammad Erias Erlangga (Faculty of Medicine, Universitas Padjadjaran, 2023)
Coronary artery bypass graft (CABG) surgery is a surgical therapy for coronary artery disease (CAD) patients who cannot be solely treated using pharmacological therapy. Patients undergoing CABG surgery require careful postoperative monitoring in the intensive care unit (ICU). This leads to the need for careful selection of patients due to the limited number of ICU beds available. A prolonged stay in ICU could delay surgery for other patients. This retrospective study analyzed how preoperative factors such as age, gender, and preoperative left ventricular ejection fraction (LVEF) may influence patient's length of stay (LOS) in the ICU. For this study, subjects were patients undergoing isolated CABG in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, during the period of January 2019- December 2020 who were selected using the simple random sampling method. The subjects were categorized into <65 years old and ≥65 years old age groups; man and woman gender; preoperative LVEF of <40% and ≥40%; and prolonged ICU LOS (>96 hours) and non-prolonged ICU LOS (<96 hours). Deceased patients in the ICU were excluded. Results of the bivariate and multivariate analyses showed that age was the only factor (p-value of 0.017) that increased the risk of prolonged ICU LOS (OR of 3.34) after CABG surgery that was statistically significant. This study concluded that patient of old age (>65 years old) is at a higher risk of having prolonged ICU LOS after CABG; thus, a careful scheduling of patients for CABG surgery by age is important to prevent prolonged ICU LOS after CABG.